The Relationship Between Tooth Brushing Behaviour and Oral Hygiene Status in the Elderly in Bantul District Yogyakarta - Utami, Sri; Claresta, Elvaretta Angie (Jurnal Kesehatan Gigi, 2025)
Background: The elderly population in Indonesia is estimated to increase to 2.1 billion by 2050. The increase in the number of elderly people causes an increase in problems due to aging. The elderly experience decreased cell function which cases physical limitations, especially in brushing their teeth. Tooth loss can also reduce the motivation of the elderly to brush their teeth. Physical limitations and decreased motivation affect tooth-brushing behavior, resulting in poor oral hygiene status. Other conditions that cause poor oral hygiene in the elderly are systemic diseases and medication use. Purpose: To determine the correlation between tooth brushing behavior and oral hygiene status in the elderly in Bantul in 2024 (Study at the Budi Luhur Nursing Home and the Madania Foundation). Method: This type of research is observational analytic with a cross-sectional design. This study took place in July 2024 and the research subjects were 42 people aged ≥ 60 years selected using total sampling. Tooth brushing behavior was measured using a questionnaire of knowledge, attitudes, and actions while oral hygiene status was measured using the Oral Hygiene Index Simplified (OHIS). Data analysis used the Chi-Square test. Result: The study found a significant correlation (p<0,05) between tooth brushing  knowledge, attitude, action, and behaviour toward oral hygiene status. Conclusion: There is a correlation between tooth brushing knowledge, attitude, action, and behavior toward oral hygiene status in the elderly in Bantul Yogyakarta (Study at Budi Luhur Nursing Home and Madania Foundation)